Clínica Médica e Cirúrgica de Pequenos Animais. - Lima, Amanda Borges Gonçalves (Universidade Federal do Tocantins, 2023)
The traineeshep was conducted at the Veterinary Hospital of the School of Veterinary Medicine and Animal Science of the Federal University of Goias (UFG-HV-EVZ) from April 22h to June 25th, totaling 348 hours. In this period, 145 clinical cases were treated. Trainees were required to follow the monitor residents in attendance, performing anamnesis, physical examination, collection of biological samples, and to monitor surgical procedures, from preoperative until release the patient. This report aims to describe the activities performed at the institution, giving special detail of three clinical cases.